Dolor en artritis reumatoide - Rivera R., Carolina (Revista Hospital Clínico Universidad de Chile, 2015)
Rheumatoid Arthritis (RA) is a systemic inflammatory disease of unknown cause that primarily affects the joints. The joint pain is most often the reason for consultation and main complaint in successive evaluations. The mechanisms of pain in these patients are not entirely clear as inactive stages of the disease, the pain is still a frequent complaint and appears at distant sites to the inflamed joint; it is postulated that there are phenomena of peripheral and central sensitization chronic pain involved would generate; this would require a change in the confrontation of the patient needing a multimodal and comprehensive approach with aggressive pharmacological alternatives that include infiltrations when required and no pharmacological actions such as physiotherapy, occupational therapy and exercise. This is how the early physiatrist assessment appears as an alternative. Then part of the mechanisms involved are reviewed, plus data showing clinical experience when evaluating a cohort of patients diagnosed with RA.